Evaluation of Community Policing Initiatives in Jefferson County, West Virginia, 1996-1997 - McCoy, Diane C. ([Verlag nicht ermittelbar], 2000)
This data collection was designed to evaluate the implementation of community policing initiatives for three police departments in Jefferson County, West Virginia: the Ranson Town Police Department, the West Virginia State Police (Jefferson County Detachment), and the Jefferson County Sheriff's Department. The evaluation was undertaken by the Free Our Citizens of Unhealthy Substances Coalition (FOCUS), a county-based group of citizens who represented all segments of the community, including businesses, churches, local law enforcement agencies, and local governments. The aim was to find answers to the following questions: (1) Can community policing have any detectable and measurable impact in a predominantly rural setting? (2) Did the police department do what they said they would do in their funding application? (3) If they were successful, what factors supported their efforts and were key to their success? and (4) If they were not successful, what problems prevented their success? The coalition conducted citizen surveys to evaluate how much of an impact community policing initiatives had in their county. In January 1996, research assistants conducted a baseline survey of 300 households in the county. Survey responses were intended to gauge residents' fear of crime and to assess how well the police were performing their duties. After one year, the coalition repeated its survey of public attitudes, and research assistants interviewed another 300 households. The research assumption was that any change in fear of crime or assessment of police performance could reasonably be attributed to these new community policing inventions. Crime reporting variables from the survey included which crime most concerned the respondent, if the respondent would report a crime he or she observed, and whether the respondent would testify about the crime in court. Variables pertaining to level of concern for specific crimes include how concerned respondents were that someone would rob or attack them, break into or vandalize their home, or try to sexually attack them/someone they cared about. Community involvement variables covered participation in community groups or activities, neighborhood associations, church, or informal social activities. Police/citizen interaction variables focused on the number of times respondents had called to report a problem to the police in the last two years, how satisfied they were with how the police handled the problem, the extent to which this police department needed improvement, whether children trusted law enforcement officers, whether police needed to respond more quickly to calls, whether the police needed improved relations with the community, and in the past year whether local police performance had improved/gotten worse. Specific crime information variables include whether the crime occurred in the respondent's neighborhood, whether he/she was the victim, if crime was serious in the respondent's neighborhood versus elsewhere, whether the respondent had considered moving as a result of crime in the neighborhood, and how personal safety had changed in the respondent's neighborhood. Variables relating to community policing include whether the respondent had heard the term "community policing" in the past year, from what source, and what community policing activities the respondent was aware of. Demographic variables include job self-classification, racial/ethnic identity, length of residency, age, gender, martial status, educational status, and respondent's town of residence.